Natural ethics and informed consent/Ética natural e consentimento livre e esclarecido - Robert D. Hinshelwood (Universidade Estadual de Campinas, 2010)
In this paper I examine one way in which psychoanalysis could contribute a natural ethics based on the inherent psychological development of a moral conscience. Psychoanalytic object-relations theories postulate the fundamental relational nature of human beings, and therefore the correlated concerns about the well-being of others. The notion of unconscious projective identification central to some theories provides an ethic of integration. Nesse artigo eu examino uma forma através da qual a psicanálise poderia contribuir com uma ética natural baseada no desenvolvimento psicológico inerente à consciência moral. As teorias psicanalíticas das relações de objeto postulam a fundamental natureza relacional dos seres humanos e, por conseguinte, sua correlata preocupação com o bem-estar dos outros. A noção de identificação projetiva inconsciente, central em algumas teorias, oferece uma ética de integração.